Community pharmacies: an ideal setting to promote continence - Gordon, D.; Howat, Peter (Continence Foundation of Australia, 2005)
Stage One of the Pharmacy Continence Care Project (the project) was undertaken in 2003-2004 by the Continence Advisory Service of WA Incorporated. The aim of the project was to establish current best practice in the provision of continence care within community pharmacies in Australia and internationally, and to develop a model of best practice based upon these findings. These materials will be trialed and evaluated in the second stage of the project. Research, including a literature search, surveys of pharmacy staff, consumer focus groups and a consumer survey was conducted. A survey of consumers found that they were generally uncertain of knowledge levels of pharmacy staff in relation to continence issues.This uncertainty was demonstrated by consumers indicating that they would primarily seek continence advice from a doctor or other health care professional rather than a pharmacist. While a definitive model was not found, components of a best practice model and opportunities to promote continence were identified. Stage one of the project concluded with the development of draft training modules. In response to input from pharmacy staff, a selection of supportive material, such as product selection guides was developed to enhance pharmacy staff skills in providing information and advice on continence care. The second stage of the project will involve the evaluation and modification of the training materials.